AXIOMS ​​TO TRANSFORM THE PERFORMANCE OF NEABI IN FEDERAL INSTITUTES IN THE NORTHEAST WITH THE USE OF DIGITAL TECHNOLOGIES: A SYSTEMATIC LITERATURE REVIEW - Lemos, Elizama das Chagas; do Nascimento, Juliana Bezerra; Santos, Rejane Cristina Borges; Gomes, Letícia da Silva (Seven Editora, 2025)
This article proposes a systematic review of the literature on Digital Information and Communication Technologies in educational contexts, specifically in the work of Centers for Afro-Brazilian and Indigenous Studies at Federal Institutes in the Northeast. Using parameters and guidelines based on the PRISMA Group, papers were selected from the Scielo bibliographic databases and the Capes repository to verify the research conducted. To this end, a bibliographic review was conducted, as well as analysis and reflection on the research findings from 2020 to 2025. The findings suggest that this is a field of study that can be increasingly expanded to utilize educational technologies to promote education based on the appreciation of Afro-Brazilian and Indigenous cultures within the NEABIs' field of action.DOI: https://doi.org/10.56238/sevened2025.029-093